Assessing City Marketing in Jordan: The Case of Petra - ALNSOUR, Jamal Ahmad; AL-WESHAH, Ghazi A.; KAKEESH, Dana F.; AL-HYARI, Khalil; ARABEYYAT, Abdullah Radwan (Journal of Environmental Management and Tourism, 2024)
The aim of this study is to assess city marketing approaches used in promoting Petra in Jordan. To this end, four major criteria, including integrated marketing communication, quality of urban services, organizational procedures, and tourism receipt, were considered in this study. A qualitative method using in-depth, face-to-face interviews with top managers, was used to achieve the study objectives. Findings reveal that Petra suffers from a lack of effective city marketing strategies. The processes of city marketing, including integrated marketing communication, urban services, organizational aspects, and financial reserves, are greatly ineffective. Such processes are basically influenced by regulations, funding, and collaboration between various public authorities, as well as between the public sector and the private sector. The study provides useful insights for policymakers in order to improve city marketing in Jordan.